The Importance of Scientific Crime Investigation (SCI) in Solving Murder Cases in Indonesia - Serlina Wulandari; Warasman Marbun; Roland Hutabarat (Justice Voice, 2025)
Criminal law in Indonesia grants law enforcement authorities the power to address violations, including the crime of murder. However, handling murder cases often faces challenges, particularly in terms of evidence and identifying the perpetrators. Technological advancements have driven the development of Scientific Crime Investigation (SCI) as a scientific approach that replaces conventional investigation methods by integrating various scientific disciplines to provide more accurate evidence. This study aims to examine the effectiveness of SCI in the investigation process and its alignment with applicable regulations. The research method employed is a normative juridical approach, referring to relevant laws and legal literature. The analysis results indicate that in Decision Number 39/Pid/2024/PT.YYK, the appellate panel of judges modified the death sentence previously imposed on the defendants in Decision Number 634/Pid.B/2023/PN.Smn to a life imprisonment sentence. This ruling suggests that the panel of judges did not adhere to Supreme Court Circular Number 05 of 1973, which regulates sentencing based on the gravity and nature of the crime.